Tiny Squares at the Hermann Grid Corners Can Completely Remove the Illusion. (February 2020) - Bakshi, Ashish; Ghosh, Kuntal
A novel modification of the Hermann grid stimulus is demonstrated. It is shown that introduction of extremely tiny squares at the corners of the grid squares in the classical stimulus, keeping the position and orientation of the grid squares fixed, can reduce the strength and even completely wipe out the illusory dark spots. The novel perturbing stimulus was investigated further and a gray-level intensity threshold was measured for the tiny corner squares beyond which the illusory blobs disappear completely. It was also found that this threshold remains practically unchanged over a wide range of grid square size for an observer.